Motivational patterns in persistent swimmers: A serial mediation analysis. Issue 5 (27th May 2020) - Teixeira, D. S.; Pelletier, L. G.; Monteiro, D.; Rodrigues, F.; Moutão, J.; Marinho, D. A.; Cid, L.
Abstract: Objective : The main objective of the present study was to examine the associations between coach-created task-involving climate and athletes' intentions to continue practicing sport, through a serial mediation analysis that included basic psychological needs satisfaction (BPN), self-determined motivation (SDM) and enjoyment. Methods : Seven-hundred and ninety-nine elite swimmers (450 males, 349 females; aged 12–22 years, M = 16.65, SD = 2.83) participated in the present study. Groups were created according to age, years of experience, and gender. Results : Serial mediation analysis provided support for the proposed model where BPN's and enjoyment represent the most important mediators between task-involving climate and athletes' intentions to continue sport practice. Conclusion : Enjoyment stands out as the most relevant predictor of intention to persist and as a significant mediator in the relation between task-involvement climate, BPN, SDM, and long-term sports practice. The task-involving climate created by coaches appears to set in motion a sequence where the satisfaction of basic needs and SDM lead to more enjoyment and increased persistence among young athletes.